The impact of sales growth, capital structure, and liquidity on the value of companies in the property sector - Yomita, Yomita; Suhardi, Suhardi; Deseria, Rita (International Enterprise Integration Association, 2025)
This study aims to examine the influence of Sales Growth, Capital Structure, and Liquidity on Company Value in the property sector listed on the Indonesia Stock Exchange (IDX). Panel data from 31 property firms over the 2019–2023 period (155 firm-year observations) were analyzed using the Random Effects Model, selected based on statistical tests to address unobserved heterogeneity across firms and time. The results indicate that Capital Structure (DER) has a significant negative effect on Company Value (PBV), supporting the Trade-Off Theory in the context of excessive debt risk under high interest rates. Liquidity (CR) has a significant positive effect, highlighting the importance of stable cash flow in sustaining firm value. Meanwhile, Sales Growth (SG) is found to be statistically insignificant, suggesting that although sales expansion may enhance firm value, post-pandemic market uncertainty causes investor skepticism regarding its sustainability. Practically, the findings imply that investors should carefully assess a firm's debt policy and liquidity strategy, while corporate managers must ensure that sales growth is supported by sustainable financing and operational efficiency rather than aggressive expansion. This study contributes to the literature by exploring the unique dynamics of Indonesia’s property sector, which is highly influenced by government policies and macroeconomic volatility. Future research is recommended to incorporate macroeconomic variables and differentiate between residential and commercial property subsectors to provide deeper insights.